Effect of space allowance with and without antibiotic on performance of weaned pigs - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1981)
Two feeding trials were conducted to evaluate 1.5, 2.5, and 3.5 sq. ft. of space allowance for the four week old weaned pig. In addition, performance of pigs fed an antibiotic (ASP 250) versus no antibiotic at each space allowance was evaluated. The pigs fed an antibiotic gained significantly faster than pigs receiving no antibiotic; however, most of the improvements were observed the first three weeks of the five week trial. Maximum growth was observed at 2.5 sq. ft. and 3.5 sq. ft. of space allowance. Pigs given 1.5 sq. ft. gained slightly slower throughout the trial. This study suggests that 2.5 sq. ft. of space (totally slatted floor) is adequate for the 4-week-old pig and thereafter until weighing approximately 45 lbs.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Antibiotics; Performance; Weaning